Effect of Imeglimin, a Novel Anti-Diabetic Agent, on Insulin Secretion and Glycemic Variability in Type 2 Diabetes Treated with DPP-4 Inhibitor: A 16-Week, Open Label, Pilot Study - Itsukaichi A; Yoshikawa F; Fuchigami A; Iwata Y; Sato G; Miyagi M; Hirose T; Uchino H (Diabetes, Metabolic Syndrome and Obesity)
Atsushi Itsukaichi,* Fukumi Yoshikawa,* Ayako Fuchigami, Yoko Iwata, Genki Sato, Masahiko Miyagi, Takahisa Hirose, Hiroshi Uchino Department of Diabetes, Metabolism and Endocrinology, Toho University Graduate School of Medicine, Tokyo, Japan*These authors contributed equally to this workCorrespondence: Hiroshi Uchino, Department of Diabetes, Metabolism, and Endocrinology, Toho University Graduate School of Medicine, 6-11-1 Omori-Nishi, Ota-ku, Tokyo, 143-8541, Japan, Tel +81-3-3762-4151, Fax +81-3-3765-6488, Email h.uchino@med.toho-u.ac.jpPurpose: Imeglimin is a novel oral antidiabetic agent that improves glucose tolerance. This study aimed to investigate the efficacy of combining imeglimin with dipeptidyl peptidase-4 inhibitor (DPP-4i), the most frequently prescribed first-line treatment for patients with type 2 diabetes (T2D) in Japan, to improve glycemic control.Patients and Methods: Eleven patients with T2D treated with DPP-4i alone (6.5% ≤ hemoglobin A1C [HbA1c] < 10%) received 1000 mg imeglimin twice daily for 16 weeks. A meal tolerance test (MTT) was conducted on seven of these patients to assess parameters associated with islet function or insulin tolerance, such as homeostasis model assessment (HOMA)-β-cell function (HOMA-β), HOMA-insulin resistance (HOMA-IR), C-peptide immunoreactivity (CPR) index, and glucagon kinetics. Continuous glucose monitoring was conducted to evaluate parameters for glycemic variability.Results: Sixteen weeks after imeglimin administration, the HbA1c level improved from 7.5%± 1.3% to 6.5%± 0.5% (p < 0.05), the casual blood glucose level significantly improved from 168.2± 55.4 to 127.8± 20.0 mg/dL (p=0.027), time in range increased from 65.0%± 0.34% to 90.0%± 0.08% (p < 0.05), and time above range reduced from 34.0%± 0.034% to 9.0%± 0.08% (p < 0.05). During MTT, we observed significantly reduced area under the curve (AUC)0– 180 glucose, increased AUC0-180 CPR/AUC0-180 glucose, CPR index, and HOMA-β (p< 0.05). HOMA-IR and glucagon kinetics did not change with the addition of imeglimin.Conclusion: The addition of imeglimin to DPP-4i significantly improved glycemic control and glycemic variability, based on increased glucose-induced insulin secretion, indicating its potential as a therapeutic option for patients with T2D.Keywords: imeglimin, DPP-4 inhibitor, time in range, glycemic variability, continuous glucose monitoring, meal tolerance test